2017
DOI: 10.1080/00016357.2017.1367959
|View full text |Cite
|
Sign up to set email alerts
|

Associations of alveolar bone loss and interleukin-1β levels in one- and two-stage surgical procedures: a randomized prospective trial

Abstract: Within the limitations of the short observational period and small sample size of this study, two-stage implant placement shows comparable clinical outcomes to implants placed using a one-stage placement protocol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…In a previous prospective, randomized controlled study carried out in 40 patients (20 patients received single TP/BL implants and 20 patients received single OP/TL implants, both in mandible), Talo Yildirim et al 14 evaluated the changes in CBL and IL‐1β levels in PICF at the implant sites before loading (T0) and during the third (T1) and sixth (T2) months after loading. Around TP/BL implants between T0 and T2, authors found a significantly higher CBL ( p < 0.05) and higher PICF IL‐1β levels, even if the latter did not show a statistically significant difference ( p > 0.05).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a previous prospective, randomized controlled study carried out in 40 patients (20 patients received single TP/BL implants and 20 patients received single OP/TL implants, both in mandible), Talo Yildirim et al 14 evaluated the changes in CBL and IL‐1β levels in PICF at the implant sites before loading (T0) and during the third (T1) and sixth (T2) months after loading. Around TP/BL implants between T0 and T2, authors found a significantly higher CBL ( p < 0.05) and higher PICF IL‐1β levels, even if the latter did not show a statistically significant difference ( p > 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest that an inflammatory stimulus could originate at the M/I, and that there could be a causal relationship between the magnitude of alveolar bone loss, and the extent of peri‐implant inflammatory status. The influence of M/I on long‐term implant success has been investigated in many experimental and clinical studies and has been the subject of literature reviews which, however, reported contradictory outcomes 1–7,13–16 . Thus, whether the location of M/I influences the degree of crestal bone resorption and the onset of peri‐implant biological complications over time is still subject of debate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the literature, IL-1 β is secreted locally during an inflammatory state, accelerating inflammatory reactions with other factors involved in the immune response [ 28 ]. Furthermore, there is some evidence suggesting that IL-1 β is the main proinflammatory biomarker in active peri-implantitis regions; thus, it can be used as an early indicator of peri-implant disease [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Before sampling, implant sites were isolated using cotton rolls and air-dried to eliminate salivary contamination. Paper strips (PerioPaper; Oraflow, NY, USA) were placed 2-3 mm into the peri-implant crevice with forceps for 30 seconds at the vestibulo-mesial and vestibulo-distal sites of each implant [ 28 ]. In case of blood contamination, the strip was discarded.…”
Section: Methodsmentioning
confidence: 99%